Kinetic-based extrapolating of methane production potential for seaweed/food waste matrixes - Yoruklu, Hulya Civelek; Demir, Ahmet; Ozkaya, Bestami (INDERSCIENCE ENTERPRISES LTD, 2020)
Seaweed accumulation result in undesirable environmental problems along the coastline of Istanbul. In this study, methane production potential of seaweed/food waste matrix was evaluated to explore how much of waste seaweed could be fed with food waste to an anaerobic digester at what rates of substrate to inoculum (S/X). Results indicated that the reactors fed with only food waste were inhibited with the S/X ratio exceeding 4 g VSsubstrate/g VSinoculum, but it could be reached up to 2,172 m(biogas)(3)/m(reactor)(3)/d in continuous-fed-system when seaweed/food waste mixture ratio increases to 2/1 at 6 g VSsubstrate/g VSinoculum. This was indicated that seaweed was a useable agent with a good buffer capacity to improve performance of digesters arising from substrate inhibition. Methane production potential data was also modelled to describe the digestion kinetics by modified Gompertz, first-order, logistic function, and transference equation models. Transference function among applied models gave the best fit to describe the kinetics of methane production potential at practical applications.
Keywords: seaweed; the Marmara Sea; food waste; kinetics; anaerobic digestion; LIFE-CYCLE ASSESSMENT; ANAEROBIC-DIGESTION; BIOGAS PRODUCTION; CO-DIGESTION; BIOMETHANE PRODUCTION; THERMAL PRETREATMENT; MARINE MACROALGAE; INOCULUM RATIO; SUBSTRATE; Environmental Sciences & Ecology